Michel Foucault estóico? - Potte-Bonneville, Mathieu (Mnemosine, 2017)
Tradução de: Michel Foucault stoïcien? Magazine Littéraire, nr. 461, fev/2007, pp.54-56. Tradutora: Heliana de Barros Conde Rodrigues.